The Semantics and Theology of Joy in the Philippians: A Revision of William G. Morrice’s Thesis On Joy - Hendi (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2022)
Joy is a fundamental doctrine in Christianity since it is the core message of the gospel and the fruit of the Spirit that distinguishes Christians' lives. William G. Morrice particularly investigated this issue, and this article tries to revise his thesis of joy to be more comprehensive. Joy must be viewed as a concept or meaning rather than a single word. With a discourse analysis approach and semantic domain, the writer tries to complete Morrice's research by improving his method, which only examines eleven synonymous words of joy. The Philippians is chosen as a sample discourse because this is the epistle of Joy from the Apostle Paul. Joy in the Philippians is a matter of relations with God (as Morrice views) and believers' relations with others (church), personal, ministry and mission, and material needs, and the environment.